Stres, Dukungan Keluarga Dan Agresivitas Pada Istri Yang Menjalani Pernikahan Jarak Jauh - Margiani, Kristin (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract. Aggressivity is a destructive behavior which can be done by anyone and anywhere. The purpose of this study to examine the relationship between stress and family support with aggressiveness at wife who underwent a long-distance marriage.Â  The subject of this study were 53 wives who underwent a long-distance marriage which have child at least one person. The data was collected using Aggressivity scale, stress scale and the scale of family support. The collected data were analyzed with a statistical technique of regression analysis and then parcial correlation. Results of regression analysis showed that there was a significant relationship between stress and family support with Aggressivity, with the effective contribution of stres and family support respectively by 23,07 % dan 45,03 %. By partial, stress variable did not correlated with aggressivity, but the family support variables significantly negatively correlated with aggressivity.Keywords : stress, family support, aggressivenessÂ